ŚMIERĆ PEŁNOMOCNIKA PROCESOWEGO W ASPEKCIE ZAWIESZENIA POSTĘPOWANIA - Kincbok, Agnieszka (Zeszyty Prawnicze, 2017)
Death of the Attorney in Context of the Stay of Proceedings Summary This article looks into the widely disputed issue whether death of the attorney is the reason to stay of proceedings or not. The author argues that on the ground of the currently binding regulations it is necessary to stay of proceedings only in the situation in which the Civil Proceedings Code provides for compulsory barrister’s or legal adviser’s counseling. But when the party can decide to assign a counsel or not, death of the attorney isn’t the reason for stay of proceedings. In this situation the judge should adjourn a trial, inform a party about the attorney’ s death and summon her.